2021
DOI: 10.3389/fonc.2021.780085
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Approaches to Chronic Lymphocytic Leukemia With High-Risk Molecular Features

Abstract: The clinical course of chronic lymphocytic leukemia (CLL) is highly variable. Over the past decades, several cytogenetic, immunogenetic and molecular features have emerged that identify patients suffering from CLL with high-risk molecular features. These biomarkers can clearly aid prognostication, but may also be capable of predicting the efficacy of various treatment strategies in subgroups of patients. In this narrative review, we discuss treatment approaches to CLL with high-risk molecular features. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 177 publications
(220 reference statements)
0
3
0
Order By: Relevance
“…This study utilized the best available public literature sources to inform a range of plausible clinical parameters in the model, but further effectiveness evidence may be required to improve the long-term clinical outcome estimates. Yet, such data will remain scarce unless clinical trials are designed to directly investigate the clinical benefit of treatment for predictive groups categorized by TP53 wildtype/aberrations and IGHV- U/ IGHV -M. These clinical trials are costly to conduct, and it is unlikely future patients with TP53 aberrations and/or IGHV- U enrolled in clinical trials will receive FCR with the shift away from this treatment for these patients [ 50 ]. Nonetheless, the trials included in the ITC analysis were comparable based on the study design, patient population and outcome measures (Table S2 in the ESM).…”
Section: Discussionmentioning
confidence: 99%
“…This study utilized the best available public literature sources to inform a range of plausible clinical parameters in the model, but further effectiveness evidence may be required to improve the long-term clinical outcome estimates. Yet, such data will remain scarce unless clinical trials are designed to directly investigate the clinical benefit of treatment for predictive groups categorized by TP53 wildtype/aberrations and IGHV- U/ IGHV -M. These clinical trials are costly to conduct, and it is unlikely future patients with TP53 aberrations and/or IGHV- U enrolled in clinical trials will receive FCR with the shift away from this treatment for these patients [ 50 ]. Nonetheless, the trials included in the ITC analysis were comparable based on the study design, patient population and outcome measures (Table S2 in the ESM).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IGHV and TP53 mutational status are currently the major theranostic markers in CLL, orienting treatment towards immunochemotherapy or chemo-free (BTKi, iBCL2) schedules (2,27,28). It would moreover be very easy to include other targets such as ATM, NOTCH1, SF3B1, BIRC3 (29) or others, should they become significant indicators of response or prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by the clonal expansion of CD5+ B-cells and mainly elderly people are affected [ 88 ]. CLL is a heterogeneous disease and most patients survive decades, while others have a rapid disease progression with poor outcome [ 89 ]. In a study of Ronchetti et al, snoRNA expression was profiled in CLL patients and different snoRNAs were identified as potential biomarkers [ 74 ].…”
Section: Dysregulation Of Snornas In Cllmentioning
confidence: 99%